2021
DOI: 10.1126/scitranslmed.abj5413
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibodies targeting distinct regions of the spike protein potently neutralize SARS-CoV-2 variants of concern

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern threatens the efficacy of existing vaccines and therapeutic antibodies and underscores the need for additional antibody-based tools that potently neutralize variants by targeting multiple sites of the spike protein. We isolated 216 monoclonal antibodies targeting SARS-CoV-2 from plasmablasts and memory B cells collected from patients with coronavirus disease 2019. The three most potent antibodies targeted distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 87 publications
5
78
0
Order By: Relevance
“…Going forward with the identification of more effective therapies against SARS-CoV-2, multiple laboratories have reported the development of bispecific antibodies by combining 2 antibodies that target nonoverlapping epitopes on the spike protein and multivalent nanobodies. These engineered molecules have been described to be highly potent in neutralizing the SARS-CoV-2 variants and suppressing mutational escape [ 119 122 ]. Alongside this, antibodies from the NTD and community RBD-1 to RBD-4 are an attractive choice for the therapeutic cocktails being more potent than others, but the data suggest that emerging SARS-CoV-2 variants tend to escape binding by many members of the groups associated with most potent neutralizers [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Going forward with the identification of more effective therapies against SARS-CoV-2, multiple laboratories have reported the development of bispecific antibodies by combining 2 antibodies that target nonoverlapping epitopes on the spike protein and multivalent nanobodies. These engineered molecules have been described to be highly potent in neutralizing the SARS-CoV-2 variants and suppressing mutational escape [ 119 122 ]. Alongside this, antibodies from the NTD and community RBD-1 to RBD-4 are an attractive choice for the therapeutic cocktails being more potent than others, but the data suggest that emerging SARS-CoV-2 variants tend to escape binding by many members of the groups associated with most potent neutralizers [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting multiple sites in the spike protein could be a promising strategy to cope with VOC as mutations in the NTD and other regions are suggested to affect the structure and thus the immunogenicity RBD epitopes [ 240 ]. In this regard, Cho et al [ 241 ] designed bispecific antibodies which potently neutralize VOC (Alpha, Beta, Gamma, and Delta variants) and the wild-type virus. In addition, combining RBD and NTD neutralizing antibodies is suggested to be another means of fighting with VOC [ [242] , [243] , [244] ].…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%
“…The nAbs recognize RBD, or other regions on the S glycoprotein, directly or indirectly interfering with the ACE2 interaction [67]. Previous studies have shown that different Abs target different regions on the S protein [68,69]. The epitome mapping studies on the Abs specific to S protein showed that 21% of the 377 epitopes were from RBD [70].…”
Section: Neutralizing Antibody Complex Analysismentioning
confidence: 99%